What to read when : the books and stories to read with your child and all the best times to read them - Allyn, Pam, 1963- (Avery, 2009)
"Award-winning educator Allyn offers parents and caregivers essential advice on choosing appropriate titles for their children--taking into account a child's age, attention ability, gender, and interests--along with techniques for reading aloud effectively."
Obsahuje rejstřík
Keywords: dětská četba; práce s dětským čtenářem; výchova ke čtenářství; dětská literatura; dětské čtenářství; doporučená četba; children's reading; assistance to child readers; readers' education; children's literature; child reading; reading lists